Tandem C–N coupling/Boulton–Katritzky rearrangement reactions of 3-aminoisoxazoles or 1, 2, 4-oxadiazol-3-amines with 2-pyridyl trifluoromethanesulfonate: a rapid access to [1, 2, 4]triazolo[1, 5-a]pyridines. Issue 13 (24th May 2022) - Xiong, Huilan; Li, Zihao; Tang, Huang; He, Lei; Zhou, Wei
Abstract : A palladium-catalyzed tandem C–N coupling/BK rearrangement reaction of 1, 2, 4-oxadiazol-3-amines or 3-aminoisoxazoles with 2-pyridyl trifluoromethanesulfonate has been achieved for the first time. Abstract : An efficient and convenient synthesis of functionalized [1, 2, 4]triazolo[1, 5- a ]pyridine derivatives is presented. The protocol involves a palladium catalyzed tandem C–N coupling/Boulton–Katritzky rearrangement process of 3-aminoisoxazoles or 1, 2, 4-oxadiazol-3-amines with 2-pyridyl trifluoromethanesulfonate. This protocol features readily available starting materials and could also be applied to the synthesis of leishmania CRK3 inhibitors.